Physiotherapy for children with hypermobility syndrome - Kerr, A; Macmillan, C; Uttley, W; Luqmani, R (2000)
Hypermobility syndrome describes the group of musculoskeletal complaints, particularly myalgia and arthralgia, that appear to be associated with non-pathological excessive joint mobility. Physiotherapy, which is frequently recommended for this syndrome, has not been defined or investigated for effectiveness. However, the experience of treating unstable joints, in particular shoulder and knee joints, provides the basis for the physiotherapy approach in this common condition. This paper describes the management programme adopted at the Royal Hospital for Sick Children, Edinburgh, that may offer a guideline for practitioners and the basis for future study. Retrospective data from this clinic support the efficacy of the programme.